A study on the jurisprudential and doctrinal approach of the Shafi'i school of thought By knowing some of his scholars (Journal of Misan Researches, 2023)
What a person needs with regard to the jurisprudential and doctrinal schools is to know their origins, the reasons for their emergence, their effects, and their scholars, and this is only done through an in-depth study of those schools, and our research deals with the Shafi’i school in particular, by identifying their jurisprudential and doctrinal approach and its conformity with what was stated in the Qur’an the honorable Sunnah; This is due to the importance of this school of thought in the scientific and social circles at the regional and international levels, and knowledge of it through its most prominent scholars on the jurisprudential and doctrinal levels, and an indication of the extent of their ability to preserve its survival and continuity.